2014
DOI: 10.4314/jmbs.v3i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and discrimination associated with HIV/AIDS in health care settings: a comparative study in two hospitals of different categories in Douala-Cameroon

Abstract: The response to the human immunodeficiency virus epidemic faces many challenges with stigma and discrimination being two of them. The aim of this study is to determine the extent of effects of stigmatization and discrimination against people living with HIV-AIDS, and the influence of the type of hospital structure, in the manifestations of stigma and discrimination. A prospective cross sectional study was conducted among a total of 400 patients, using a pre-tested questionnaire. An observation form was also fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(19 reference statements)
4
4
2
Order By: Relevance
“…This result is similar to that of Onoya et al in South Africa [17] and confirms the fact that having more sexual partners is a risk factor for HIV/AIDS in general [18].…”
Section: Infection Rate Of Hiv Of Pygmies In the Workplacesupporting
confidence: 91%
“…This result is similar to that of Onoya et al in South Africa [17] and confirms the fact that having more sexual partners is a risk factor for HIV/AIDS in general [18].…”
Section: Infection Rate Of Hiv Of Pygmies In the Workplacesupporting
confidence: 91%
“…This level of discrimination in the present study was similarly observed in studies done in Cameroon [17] and Madagascar [18] where 26% and 36% of the patients reported having been victims of discrimination respectively. The level of education and the socioeconomic status of the respondents, may also have contributed to their level of knowledge of stigmatization and hence, could have influenced what was regarded as discrimination by the respondents.…”
Section: Discussionsupporting
confidence: 77%
“…Also, with respect to occupation, even though it is not unusual in our environment for a mandatory HIV test before employment, it is quite unusual for employees in the public sector to be mandated to do a HIV test, and this, coupled with the unlikelihood of HIV status disclosure, may be an explanation why the respondents who are employed as civil servants with undisclosed HIV status were less likely to have reported discrimination. Furthermore, though the present study observed a similar lack of association between gender and discrimination with a previous study in Cameroon [17], the relationship between age and discrimination was not consistently observed.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Stigma related to the human immunodeficiency virus (HIV) is prevalent and has been identified to be a major barrier for HIV prevention and treatment [1]. Researchers suggest that HIV-related stigma is also still a barrier for people living with HIV (PLWH) to disclose their HIV status and to seek and adhere to treatments; consequently, this barrier has an adverse impact on their health [2][3][4]. HIVrelated stigma exists in nursing care worldwide and has large impact on the health outcomes of PLWH [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%